Esophageal Adenocarcinoma: Impact of a Large Hiatal Hernia on Outcomes After Surgery. Issue 5 (November 2016) - Gandon, Anne; Gronnier, Caroline; Renaud, Florence; Borde, Paul; Vanderbeken, Marguerite; Hec, Flora; Piessen, Guillaume; Adenis, Antoine; Mirabel, Xavier; Mariette, Christophe
Abstract : Objective: To evaluate complete tumor resection rate (primary objective), 30-day postoperative outcomes, and survival (secondary objectives) in patients with a hiatal hernia (HH)≥ 5 cm (HH group) compared with those who did not have a HH or presented with a HH <5 cm (control group). Background: HH is a risk factor for esophageal and junctional adenocarcinoma (EGJA). Its impact on the outcomes after EGJA surgery is unknown. Methods: Among 367 patients who underwent surgery for EGJA, a HH was searched for on computerized tomography scan and barium swallow, with comparison between the HH (n = 42) and control (n = 325) groups. Results: In the HH group, EGJAs exhibited higher rates of incomplete resection (50.0% vs 4.0%; P < 0.001), of pN3 stages (28.5% vs 10.1%; P = 0.002), and lower median survival (20.9 vs 41.0 mos; P = 0.001). After adjustment, a HH ≥5 cm was a predictor of incomplete resection (odds ratio 21.0, 95% confidence interval 9.4–46.8, P < 0.001) and a poor prognostic factor (hazard ratio 1.6, 95% confidence interval 1.1–2.5, P = 0.025). In the HH group, 30-day mortality was significantly higher in patients who received neoadjuvant radiotherapy (20.0% vs 0%; P = 0.040), which was related to greater cardiac and pulmonary toxicity. Conclusions: For the first time, we showed that a HH ≥5 cm is associated with a poor prognosis in patients who had surgery for EGJA, linked to greater incomplete resection and lymph node involvement. Neoadjuvant radiotherapy was associated with a significant toxicity in patients with a HH ≥5 cm. Abstract : Supplemental Digital Content is available in the text